Formation of Religious Character Behind the Naming of the Arabic Language in the Ma’had Al-Jami’ah Center Environment of UIN Maliki Malang - Inayatur Rosyidah; Nurhadi; Moh. Saleh (Attanwir : Jurnal Keislaman dan Pendidikan, 2024)
The practice of naming several terminologies using Arabic in social dynamics at the centre of ma'had al-Jami'ah UIN Maliki Malang is very diverse, almost found in all joints of ma'had community life or in other words, the spirit of Arabic has long breathed in the soul of ma'had al-Jami'ah. Arabic naming in the ma'had al-Jami'ah environment is an identity negotiation to build a religious identity with the frame of pesantren culture. While the influence of linguistic identity behind the practice of Arabic naming is to build a Scientific-Religious Bi'ah Islamiyah and a form of global differentiation of the University brand.